KEBIJAKAN PENANGGULANGAN KEMISKINAN - Zulkifli Siregar (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2020)
This article is a multidimensional study related to various causes of poverty and some policies that can be done to handle the Kemiskina. Poverty is a very complex multidimensional problem, not just a matter of income, but also about the vulnerability and insecurity of people or groups of people, both men and women to be poor. This dimension is measured by monetary value, although the price is always changing depending on the inflation rate. The social and cultural dimension sees poverty as a institutionalization and preservation of apathy, apolitical, fatalistic, helical and other values. The dimension of poverty implicates the efforts to define poverty, including measures used. In general poverty is seen as a condition where a person or a family is in a state of deficiency and or unworthiness of life according to certain standards, human physical inadequation or inadequacy, the absence or lack of In obtaining minimal service in various areas of life, as well as difficult or lacking access in policy-making processes.There are four factors causing poverty, cultural factor, structural factor (Structural Factor), Natural factor (Natural Factor), political social conflict. The poverty alleviation policy can be seen through the 5 approaches, basic needs approach, income approach, basic approach (Human Capability Approach), objective approach, Subjective approach